Activity‐dependent regulation of NMDA receptors in substantia nigra dopaminergic neurones. (31st January 2014) - Wild, Angela R.; Jones, Susan; Gibb, Alasdair J.
<x xml:space="preserve">Abstract</x> Key points Calcium ion influx through N‐methyl‐d‐aspartate receptors (NMDARs) may contribute to substantia nigra pars compacta (SNc) dopaminergic neurone dysfunction in Parkinson's disease. Responses of NMDARs in dopaminergic neurones showed use‐dependent run‐down that was not readily reversible and was partly dependent on Ca2+ influx and partly dependent on clathrin‐mediated endocytosis. Thus, we report regulation of NMDARs in SNc dopaminergic neurones by intracellular Ca2+ at both synaptic and extrasynaptic sites and provide evidence for activity‐dependent changes in receptor trafficking. Abstract N‐Methyl‐d‐aspartate receptors (NMDARs) are Ca2+‐permeable glutamate receptors that play a critical role in synaptic plasticity and promoting cell survival. However, overactive NMDARs can trigger cell death signalling pathways and have been implicated in substantia nigra pars compacta (SNc) pathology in Parkinson's disease. Calcium ion influx through NMDARs recruits Ca2+‐dependent proteins that can regulate NMDAR activity. The surface density of NMDARs can also be regulated dynamically in response to receptor activity via Ca2+‐independent mechanisms. We have investigated the activity‐dependent regulation of NMDARs in SNc dopaminergic neurones. Repeated whole‐cell agonist applications resulted in a decline in the amplitude of NMDAR currents (current run‐down) that was use dependent and not readily reversible. Run‐down was reduced by increasing intracellular Ca2+ buffering or by reducing Ca2+ influx but did not appear to be mediated by the same regulatory proteins that cause Ca2+‐dependent run‐down in hippocampal neurones. The NMDAR current run‐down may be mediated in part by a Ca2+‐independent mechanism, because intracellular dialysis with a dynamin‐inhibitory peptide reduced run‐down, suggesting a role for clathrin‐mediated endocytosis in the regulation of the surface density of receptors. Synaptic NMDARs were also subject to current run‐down during repeated low‐frequency synaptic stimulation in a Ca2+‐dependent but dynamin‐independent manner. Thus, we report, for the first time, regulation of NMDARs in SNc dopaminergic neurones by changes in intracellular Ca2+ at both synaptic and extrasynaptic sites and provide evidence for activity‐dependent changes in receptor trafficking. These mechanisms may contribute to intracellular Ca2+ homeostasis in dopaminergic neurones by limiting Ca2+ influx through the NMDAR.